Akuntansi Perbankan Syariah pada SMK LP3 Istana Jakarta Selatan - Rahmi, Mira; Priyanto, Toni; Gunaedi Argo, Jenji (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Vocational high school (SMK) is design to set student ready to work after their finish their senior educational level. However, the current curriculum of SMK not yet design for the sharia competency. In reality, lack of knowledge of sharia were exist on students and also the teachers. Huge demand in sharia industry is not an issue for vocational high school due to the lack system and human resources. One of solution that are given by FEB UPN "Veteran" Jakarta team is socialize the sharia knowledge to SMK LP3 ISTANA, Pondok Labu, South Jakarta. The team introduced sharia banking knowledge in order to give insight opportunity for sharia banking industry, the subject given related to accounting simulation on sharia banking transaction. The action taken by The Community Service (PKM) FEB UPN "Veteran" Jakarta, were dedicated to help education community (SMK LP3 ISTANA) gets ready in preparing sharia opportunity as their skill concept for their graduated. Based on the evaluation of the results of PKM activities, the knowledge of the participants (students) SMK about Islamic banking are increase, especially regarding the accounting transactions. Furthermore there will be a visit program to the Mini's Banking FEB UPNVJ is projected to be implemented.